Genomics-Assisted Plant Breeding in the 21st Century: Technological Advances and Progress - Kumpatla, Siva P.; Buyyarapu, Ramesh; Abdurakhmonov, Ibrokhim Y.; Mammadov, Jafar A. (IntechOpen, 2012)
None